INTERNALISASI NILAI KARAKTER ANAK MELALUI PENGULANGAN SURAT AL-FATIHAH: SEBUAH SINTESIS KOMPREHENSIF BERDASARKAN NEUROSAINS, PSIKOLOGI PENDIDIKAN, DAN TEOLOGI ISLAM - Isrun Abdurahman; Rohman Pranoto; Agus Salim; Rizaldy Alpiansyah; Irfan Alkhotiri (Labina : Journal of Islamic Education Management, 2026)
This research is a Systematic Literature Review (SLR) aimed at analyzing and synthesizing findings from various studies regarding the internalization of children's character values through the repetition of Surat Al-Fatihah in prayer, as well as identifying existing research patterns, consensuses, and gaps. The synthesis results indicate that Surat Al-Fatihah contains comprehensive character values, encompassing spiritual-moral, socio-leadership, and educational aspects. The repetition of Al-Fatihah recitation acts as a mechanism for value internalization through the processes of neuroplasticity and habit formation. This paper bridges Islamic theological studies with cutting-edge discoveries in cognitive psychology and neurobiology to provide an operational foundation for children's character education in the modern era.